Hybrid Hippopotamus Optimization Algorithm–Based Energy‐Efficient Stable Cluster Construction Protocol for Data Routing in VANETs - Krishna Meera, V.; Balasubramanian, C.; Praveen, R. (International journal of communication systems, 2025)
ABSTRACT The sparse distribution as well as high‐speed characteristics of vehicular nodes on roads is determined to impact the dynamism of vehicular ad hoc network (VANET). This dynamism of VANETs introduces major challenges during the process of packet routing that introduces network fragmentation such that scalable, reliable, and robust communication can be established in an extremely dense network. Clustering of vehicular nodes is considered the potential solution that helps in handling the issues of scalability. However, the existing clustering approaches observed in the literature introduce imbalanced load balancing and maximized number of clusters in a vehicular environment. The employment of nature‐inspired meta‐heuristic algorithms is determined to be ideal for determining optimal clusters in this problem of multi‐objective combinatorial optimization. In this paper, hybrid Hippopotamus Optimization Algorithm (HPOA)–based energy‐efficient stable cluster construction protocol (HHPOASCCP) is proposed for constructing an optimized number of vehicular node clusters. The inherent parameters of HPOA helped in maintaining a proper balance between the phases of exploitation and exploration such that a globally optimal solution that represents optimal vehicular clusters is determined without the issue of local optima. This proposed clustering approach determined optimized numbers of clusters and potentially high fitness valued vehicular nodes as cluster heads (CHs) such that energy efficiency is maximized in the network. Simulation results of this propounded HHPOASCCP confirmed selected 24.38% of the nodes as the CHs, minimized number of clusters by 24.58%, maximized load balancing by 23.12%, and reduced energy consumption by 19.84% in contrast to baseline schemes. Hybrid Hippopotamus Optimization Algorithm (HPOA)–based energy‐efficient stable cluster construction protocol (HHPOASCCP) is proposed for constructing an optimized number of vehicular node clusters. Inherent parameters of HPOA helped in maintaining a proper balance between exploitation and exploration, resulting in a globally optimal solution that depicts optimal vehicular clusters without the issue of local optima. Simulation results of this propounded HHPOASCCP confirmed selected 24.38% of the nodes as the CHs, minimized number of clusters by 24.58%, maximized load balancing by 23.12%, and reduced energy consumption by 19.84% in contrast to baseline schemes.